Refining the Nasal Dorsum with Free Diced Cartilage - Hoehne, Julius; Gubisch, Wolfgang; Kreutzer, Christian; Haack, Sebastian (Facial Plastic Surgery, 2016)
Refining the nasal dorsum has become a major challenge in modern rhinoplasty as irregularities of the nasal dorsum account for a significant number of revision surgeries. In our department, free diced cartilage is now routinely applied for smoothening of the nasal dorsum. In this retrospective study, the outcomes with regard to irregularities or contour deficits of the nasal dorsum of 431 rhinoplasty cases operated by a single surgeon between July 2013 and June 2015, using free diced cartilage, are compared with 327 cases operated by the same surgeon between January 2007 and December 2008, before the introduction of the free diced cartilage technique. A decrease in early revision surgeries (i.e., revision within the 2-year period evaluated) due to dorsal irregularities or contour deficits is seen. Being a quick, easy, and highly cost-effective procedure, we feel that free diced cartilage is currently the ideal technique for refinements of the nasal dorsum.
Keywords: rhinoplasty; free diced cartilage; nasal dorsum